SARS-CoV-2 specific immune responses in overweight and obese COVID-19 patients - Onyango, Therese Bredholt; Zhou, Fan; Bredholt, Geir; Brokstad, Karl A.; Lartey, Sarah; Mohn, Kristin G.-I.; Özgümüs, Türküler; Kittang, Bård Reiakvam; Linchausen, Dagrun Waag; Shafiani, Shahin; Elyanow, Rebecca; Blomberg, Bjørn; et al. (Frontiers in Immunology, 2023)
Obesity is a known risk factor for severe respiratory tract infections. In this prospective study, we assessed the impact of being obese or overweight on longitudinal SARS-CoV-2 humoral and cellular responses up to 18 months after infection. 274 patients provided blood samples at regular time intervals up to 18 months including obese (BMI ≥30, n=32), overweight (BMI 25-29.9, n=103) and normal body weight (BMI 18.5-24.9, n=134) SARS-CoV-2 patients. We determined SARS-CoV-2 spike-specific IgG, IgA, IgM levels by ELISA and neutralising antibody titres by neutralisation assay. RBD-and spike-specific memory B cells were investigated by ELISpot, spike-and non-spike-specific IFN-γ, IL-2 and IFN-γ/IL-2 secreting T cells by FluoroSpot and T cell receptor (TCR) sequencing was performed. Higher BMI correlated with increased COVID-19 severity. Humoral and cellular responses were stronger in overweight and obese patients than normal weight patients and associated with higher spike-specific IgG binding titres relative to neutralising antibody titres. Linear regression models demonstrated that BMI, age and COVID-19 severity correlated independently with higher SARS-CoV-2 immune responses. We found an increased proportion of unique SARS-CoV-2 specific T cell clonotypes after infection in overweight and obese patients. COVID-19 vaccination boosted humoral and cellular responses irrespective of BMI, although stronger immune boosting was observed in normal weight patients. Overall, our results highlight more severe disease and an over-reactivity of the immune system in overweight and obese patients after SARS-CoV-2 infection, underscoring the importance of recognizing overweight/obese individuals as a risk group for prioritisation for COVID-19 vaccination.